Manual of structural kinesiology - Floyd, R. T (McGraw-Hill Education, 2015)
"Explaining the process of human movement, Manual of Structural Kinesiology gives a straightforward view of human anatomy and its relation to movement. The manual clearly identifies specific muscles and muscle groups and describes exercises for strengthening and developing those muscles. Manual of Structural Kinesiology provides important information in an accessible format through a combination of logical presentation, illustrations, and concise writing style"--
Keywords: Kinesiology, Applied; kineziologie aplikovaná; Complementary Therapies; Musculoskeletal Manipulations; rehabilitační a fyzikální medicína; muskuloskeletální manipulace; komplementární terapie